A Convenient Alumination of Functionalized Aromatics by Using the Frustrated Lewis Pair Et3Al and TMPMgCl⋅LiCl. Issue 43 (11th September 2013) - Unsinn, Andreas; Wunderlich, Stefan H.; Jana, Anukul; Karaghiosoff, Konstantin; Knochel, Paul
Abstract A straightforward and efficient alumination of functionalized arenes by using the frustrated Lewis pair Et3Al and TMPMgCl⋅LiCl (TMP=2, 2, 6, 6‐tetramethylpiperidyl) has been developed. In particular, halogenated electron‐rich aromatics can be smoothly functionalized by using the frustrated Lewis pair Et3Al and TMPMgCl⋅LiCl. Compared with previously described alumination methods, this procedure avoids extensive cooling and the need for an excess of base. This in situ procedure has proven to be most practical and allows for regio‐ and chemoselective metalation of a wide range of aromatics with sensitive functional groups (CONEt2, CO2Me, CN, OCONMe2) or halogens (F, Cl, Br, I). The resulting aromatic aluminates, which were characterized by using NMR spectroscopy, were subjected to allylations, acylations, and palladium‐catalyzed cross‐coupling reactions after transmetalation to zinc. It was shown that the nature of the Zn salt used for transmetalation is crucial. Thus, compared with ZnCl2 (2 equiv), the use of Zn(OPiv)2 (2 equiv; OPiv=pivalate) allows the subsequent quenching reactions to be performed with only a slight excess of electrophile (1.2 equiv) and provides interesting functionalized aromatics in good yields.